Implication of sestrin3 in epilepsy and its comorbidities. Issue 1 (9th October 2020) - Lovisari, Francesca; Roncon, Paolo; Soukoupova, Marie; Paolone, Giovanna; Labasque, Marilyne; Ingusci, Selene; Falcicchia, Chiara; Marino, Pietro; Johnson, Michael; Rossetti, Tiziana; Petretto, Enrico; Leclercq, Karine; et al.
Abstract: Epilepsy is a serious neurological disorder affecting about 1% of the population worldwide. Epilepsy may arise as a result of acquired brain injury, or as a consequence of genetic predisposition. To date, genome-wide association studies and exome sequencing approaches have provided limited insights into the mechanisms of acquired brain injury. We have previously reported a pro-epileptic gene network, which is conserved across species, encoding inflammatory processes and positively regulated by sestrin3 (SESN3). In this study, we investigated the phenotype of SESN3 knock-out rats in terms of susceptibility to seizures and observed a significant delay in status epilepticus onset in SESN3 knock-out compared to control rats. This finding confirms previous in vitro and in vivo evidence indicating that SESN3 may favour occurrence and/or severity of seizures. We also analysed the phenotype of SESN3 knock-out rats for common comorbidities of epilepsy, i.e., anxiety, depression and cognitive impairment. SESN3 knock-out rats proved less anxious compared to control rats in a selection of behavioural tests. Taken together, the present results suggest that SESN3 may regulate mechanisms involved in the pathogenesis of epilepsy and its comorbidities. Abstract : We previously identified a pro-epileptic gene network positively regulated by sestrin3 (SESN3). Here, we found that SESN3 knock-out rats have decreased susceptibility to seizures and reduced propensity to anxiety, suggesting that SESN3 may regulate mechanisms causally involved in the pathogenesis of both epilepsy and its comorbidities. Graphical Abstract: